Item, semantic and operational equivalence of the “Musicing: Forms of Activity, Stages and Qualities of Engagement Scale” (Orfeu, 2020)
In the 1960s, the researchers Nordoff and Robbins started develop scales in order to assess music therapy services. Among them the “Musicing: Forms of Activity, Stages and Qualities of Engagement Scale”. This scale was developed to evaluate subtleties present in the musical production from a patient taking part on music therapy service. In Brazil, there is a great demand for validated measurement instruments in Brazilian language. In order to contribute to the validation in the Brazilian music therapy context, this work aims to evaluate the translation of this scale and its respective explanatory manual. As a methodology, we performed 3 steps from the Universalist Validation Model developed by Herdman, Fox-Hushby and Badia (1998), named item equivalence, semantic equivalence and operational equivalence. Six translators participated in this study in the initial stage and 9 evaluators in the translation perused the process. “Musicing: Forms of Activity, Stages and Qualities of Engagement Scale” and its respective explanatory manual were used as instruments. For this study, a Form for the analysis of the Translations and a Questionnaire for Analysis of the Items, Semantics and Operational Equivalences were prepared. According to the analysis of the responses collected from the evaluators, the translation of this scale has understandable language, their items are relevant to the Brazilian context and may contribute to future research in music and music therapy.
Keywords: Field recording; listening; urban walks; negative spaces; opaque spaces